Answer:
1. x + 3
2. x - 1
3. x + 5
4. x + 4
Explanation:
1. If f(x) = x² - 9 and g(x) = x - 3, then h(x) = f(x) ÷ g(x) = (x² - 9) ÷ (x - 3) = [(x + 3)(x - 3)] ÷ (x - 3) = x + 3
2. If f(x) = x² - 4x + 3 and g(x) = x - 3, then h(x) = f(x) ÷ g(x) = (x² - 4x + 3) ÷ (x - 3) = [(x - 1)(x - 3)] ÷ (x - 3) = x - 1
3. If f(x) = x² + 4x - 5 and g(x) = x - 1, then h(x) = f(x) ÷ g(x) = (x² + 4x - 5) ÷ (x - 1) = [(x - 1)(x + 5)] ÷ (x - 1) = x + 5
4. If f(x) = x² - 16 and g(x) = x - 4, then h(x) = f(x) ÷ g(x) = (x² - 16) ÷ (x - 4) = [(x - 4)(x + 4)] ÷ (x - 4) = x + 4. (Answer)